689 ATRC-101 Drives Potent Single-Agent Activity in Mouse Syngeneic Tumor Models via a Novel Cellular Mechanism of Action. (10th December 2020) - Leung, Yvonne; Vad, Nikhil; Ye, Anne; Santos, Daniel; Cao, Wei; Czupalla, Cathrin; Vivian, John; Williams, Carlene; Sapugay, Judevin; Harbell, Michael; Lippow, Shaun; Carroll, Chantia; et al.
Abstract : Background: We have previously demonstrated adaptive antibody responses targeting public tumor antigens in cancer patients. ATRC-101, a clinical stage, engineered version of an antibody identified in such a patient, displays robust single-agent activity in syngeneic tumor models requiring Fc receptors (FcRs) expressed by innate immune cells and the presence of CD8+ T cells. The novel target of ATRC-101 was found to be a tumor-restricted ribonucleoprotein (RNP) complex, and because RNP complexes drive T cell responses in infectious and autoimmune disease via innate immune cells, we further characterized the mechanism-of-action of ATRC-101. Here we describe changes in immune cell populations in a tumor model proximal to treatment initiation with ATRC-101. Methods: Mice bearing EMT6 tumors received ATRC-101 beginning on day 7 post-tumor inoculation. Tissues were harvested between days 7 and 14 and analyzed by flow cytometry and immunohistochemistry. Transcriptome analysis was performed using RNA sequencing on whole tumors taken on days 7, 9, and 12. Results: The earliest significant changes induced by ATRC-101, relative to vehicle, were noted just 24 hours after dosing: increased numbers of cDC1 cells in blood, and decreased numbers of cDC2 cells in blood and M-MDSCs in tumor. A significant increase of CD8+ T cells was observed in blood 48 hours after dosing and in tumor 96 hours after dosing. Increased numbers of NK cells were also observed in blood and tumor at this later time. Multiplex analysis of circulating cytokines demonstrated a very early increase in myeloid chemo-attractants, such as MCP1 and MIP1a.Whole exome sequencing of tumor samples showed that ATRC-101 dosing drives a significant increase, relative to vehicle, in the expression of interferon-stimulated genes. Co-culturing experiments demonstrated that induced, bone marrow-derived dendritic cells are activated by ATRC-101 and its target in a dose-dependent fashion. Conclusions: Dosing with ATRC-101 in the EMT6 syngeneic tumor model, in which ATRC-101 displays notable single-agent activity, leads to changes in immune cell composition in the blood and tumor, with the earliest changes observed in myeloid or myeloid-derived cell populations, and to the early appearance of myeloid chemo-attractants. We believe these data indicate that ATRC-101 acts proximally on the myeloid cell populations in the tumor, leading to a remodeling of the tumor environment and an adaptive immune response that includes CD8+ T cells driving tumor regression. Our data demonstrate that ATRC-101, bound to its target which is an RNP complex, can activate myeloid cells and are consistent with this activation occurring via FcR and Toll-like receptor (TLR) pathways.